A new species of Hoplacephala Macquart (Diptera: Sarcophagidae) from Namibia, with a discussion of generic monophyly - Pape, Thomas (Zootaxa, 2006)
A new species, Hoplacephala oryx sp. nov., is described from Namibia, Khorixas district. The male is characterized by a remarkably elongated pair of straight frontal setae and a tuft of lanceolate marginal setae on abdominal tergite 4. Generic assignment is argued from a cladistic analysis, and the monophyly of Hoplacephala Macquart is shown to be corroborated by the autapomorphic pattern of strong katepisternal setae.